The safety and efficacy of direct oral anticoagulants among chronic kidney disease patients on dialysis with non-valvular atrial fibrillation: a meta-analysis - Mapili, Jerahmeel Aleson L.; Lim, Lloyd Christopher S.; Velando, Bianca M.; Aherrera, Jaime Alfonso M. (Frontiers in Cardiovascular Medicine, 2023)
Background Individuals with chronic kidney disease (CKD) on dialysis are at an increased risk of stroke and embolic events especially in the presence of atrial fibrillation (AF). Vitamin K antagonists (VKA), including warfarin, have been used for decades for anticoagulation among CKD patients on dialysis with AF but recent evidence has shown increased bleeding. Direct oral anticoagulants (DOAC) have been emerging as an alternative to VKA which, based on several observational cohort studies, are at least as efficacious and safe as VKA. This meta-analysis looked into the safety and efficacy of DOACs compared to VKA among CKD patients on dialysis with non-valvular AF.This study used a random-effects meta-analysis using RevMan 5.4. PubMed, EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and ClinicalTrials.gov were searched from their dates of inception to June 2023. The risk of bias was assessed using Cochrane RoB2 and the certainty of evidence was assessed using GRADE.This meta-analysis showed that DOACs when compared to VKA have no significant difference in terms of risk for major bleeding (RR=0.81, 95% CI 0.46-1.43), ischemic stroke (RR=0.5, 95% CI 0.19-1.35), and cardiovascular death (RR=1.34, 95% CI 0.69-2.60).This meta-analysis adds to the growing body of evidence supporting that the use of DOACs has similar efficacy and safety outcomes in CKD patients on dialysis with non-valvular AF patients compared to VKA. The findings need to be replicated in larger and more adequately powered clinical trials in order to ascertain its level of evidence.